Mutations in SARS-CoV-2 nucleocapsid in variants of concern impair the sensitivity of SARS-CoV-2 detection by rapid antigen tests - Hagag, Ibrahim T.; Pyrc, Krzysztof; Weber, Saskia; Balkema-Buschmann, Anne; Groschup, Martin H.; Keller, Markus (Frontiers in Virology, 2022)
Rapid antigen tests (RATs) are used as convenient SARS-CoV-2 tests to minimize infection risks in the private and public domain (e.g., access to shops, concerts, sports, and other social events). RATs are: however, less sensitive than quantitative reverse transcription Polymerase chain reaction (RT-qPCR) assays; hence, samples with low viral loads may be misdiagnosed. Reports on the ability of RATs to detect SARS-CoV-2 variants of concern (VOCs) Delta and Omicron are often only qualitative. We, therefore, examined the analytical sensitivities of four different RATs for the detection of both full virus and recombinant proteins of relevant VOCs. Since most RATs are based on the detection of the SARS-CoV-2 nucleocapsid protein (N-protein), we constructed multiple N-protein mutants (mirroring specific amino acid exchanges of VOC N-proteins) using prokaryotic expression plasmids and site-directed PCR mutagenesis. Testing of recombinant proteins by four RATs revealed amino acid substitutions R203K and R203M, are critical for the sensitivity of some RATs. Interestingly, R203M mutation completely abrogated antigen detection even at high protein concentrations in the Delta variant. As a proof-of-concept study, we show that one or two specific amino acid changes in the N-protein can negatively impact the analytical sensitivity of RATs. Hence, antibodies used in such lateral flow assays should be optimized and target preferentially more conserved regions of N-protein.